PENGARUH MOTIVASI, DISIPLIN KERJA, DAN PELATIHAN KERJA TERHADAP KINERJA KARYAWAN (Studi Pada Karyawan PT Geo Dipa Energi Unit 2 Dieng Desa Pakisan) - Ahmad Akbar AP, 12.05.51.0065 (Students Journal of Economic and Management, 2016)
Each company is in desperate need of qualified human resources to achieve corporate objectives that have been determined. Willingness and skill is not effective enough to do something without a clear understanding of what will be done and how to do it. This study analyzed the influence of motivation, work discipline, and job training to employees performance at employees of PT Geo Dipa Energi Dieng. The purpose of this study was to analyze the influence of motivation, work discipline, and job training to employees performance at employees of PT Geo Dipa Energi Dieng. The sampling technique in this study using purposive sampling method for selecting the 95 respondents in the sample data collection method using a questionnaire by distributing questionnaires to the respondents in order to obtain information. Data were analyzed using factor analysis to test the validity of the question items, Cronbach alpha formula to test the reliability of each independent variable in the regression analysis test. The results of the research are: (1) Motivation has a positive and significant impact on the performance of employees (2) Discipline of work and significant positive effect on employee performance (3) Job training and significant positive effect on employee performance. Keywords: Motivation, Work Discipline, Job Training and Employee Performance.